Tube construction by a tanaidacean crustacean using a novel mucus secretion system involving the anal opening - Kakui, Keiichi (Zoological Lett, 2017)
BACKGROUND: Animals in diverse aquatic groups construct tubes using mucus and filaments, and the acquisition of this capability has likely played an important role in the evolution and diversification of small benthic animals. Tanaidacea is a crustacean order that includes tube-constructing species, most of which belong to Tanaidoidea and Paratanaoidea, with a few in Kalliapseudidae (Apseudoidea). Two previously reported systems used in tube construction are the thoracic-gland system, with secretory glands in thoracic segments (pereonites), and the pereopodal-gland system, with glands in pereopods. RESULTS: Parapseudidae (Apseudoidea) also includes a tube-constructing species, Parapseudes algicola (Shiino, 1952), which lacks large secretory glands in all pereonites and pereopods, but has a pair of acinar glands in the pleotelson, lateral to the gut. Each gland connects to the gut via a short duct, and thence to the exterior via the anal opening. Secretions released from these glands are used to construct tubes, and contain acidic and neutral mucopolysaccharides. CONCLUSION: We report in P. algicola a third, novel secretory system, here termed the pleotelsonal-gland system, used for tube construction in Tanaidacea. It is similar to the secretory system in some “thalassinidean” decapods; both systems have secretory glands connecting to the gut and thence to the anal opening as the outlet; however, these gland systems likely evolved independently. Recent discoveries of novel secretory systems for tube construction in Tanaidacea suggest that information from smaller, less well-known groups will be necessary to understand how acquisitions of tube-constructing capability affected diversification in animals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40851-017-0082-7) contains supplementary material, which is available to authorized users.